2011
DOI: 10.1002/aic.12785
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of dimethyl oxalate to ethylene glycol on a Cu/SiO2/cordierite monolithic catalyst: Enhanced internal mass transfer and stability

Abstract: in Wiley Online Library (wileyonlinelibrary.com).The design and application of a Cu/SiO 2 -based monolithic catalyst for hydrogenation of dimethyl oxalate (DMO) to ethylene glycol (EG) is presented. The catalyst was dip-coated on cordierite with highly dispersed Cu/SiO 2 slurry prepared by ammonia evaporation method. This structure guarantees high dispersion of copper species within the mesopores of silica matrix in the form of copper phyllosilicate. The catalyst is low cost, stable, and exhibits high activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
91
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 70 publications
1
91
2
Order By: Relevance
“…4 A kind of Cu/SiO 2 /Cordierite monolithic catalyst was also studied by Ma et al, 5 and their results showed that the regular channel structure and the uniform distribution of flow of the monolithic catalyst were responsible for the improved thermal stability. Modification with boron on the surface of the Cu/SiO 2 catalysts shows great enhancement in the catalytic stability on account of maintaining the balance of Cu 0 and Cu + distribution and the retarding surface transmigration of copper nanoparticles.…”
mentioning
confidence: 99%
“…4 A kind of Cu/SiO 2 /Cordierite monolithic catalyst was also studied by Ma et al, 5 and their results showed that the regular channel structure and the uniform distribution of flow of the monolithic catalyst were responsible for the improved thermal stability. Modification with boron on the surface of the Cu/SiO 2 catalysts shows great enhancement in the catalytic stability on account of maintaining the balance of Cu 0 and Cu + distribution and the retarding surface transmigration of copper nanoparticles.…”
mentioning
confidence: 99%
“…Much higher selectivity of PDO (∼30%) was obtained when using xylitol as a feedstock . Similar problems also exist in EG synthesis through catalytic hydrogenation of coal‐based dimethyl oxalate, which has been commercialized in China in recent years …”
Section: Introductionmentioning
confidence: 79%
“…The reaction generating ethylene glycol (EG) occurs in two major steps [6,7], having as an intermediary methyl glycolate (MG): (AEH) method [15] and copper-phyllosilicate core-sheath nanoreactor using hydrothermal methods [16]. This research is aimed at designing a method that can be scaled up for synthesis of Cu/SiO 2 as an industrial catalyst for dimethyl oxalate (DMO) hydrogenation to ethylene glycol (EG).…”
Section: Introductionmentioning
confidence: 99%